2022
DOI: 10.3389/fpubh.2022.827089
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, knowledge and attitude toward electronic cigarette use among male health colleges students in Saudi Arabia—A cross-sectional study

Abstract: BackgroundHealth care professionals have an important role in increasing awareness about smoking harms and serving as role models. This study aims to assess knowledge, attitude and perception toward electronic cigarettes (ECs) as well as prevalence of ECs use among male health colleges students.MethodThis is a cross-sectional survey-based study conducted among students in the male campus of five different health colleges over a 4-month period from February 2020 to May 2020. Descriptive analysis was used to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…The most frequent reason was the perceived better taste of e-cigarettes compared with traditional cigarettes. In agreement with other studies, around a third of the students considered vaping safer and cheaper than traditional smoking [23][24][25] . Moreover, around one-third of the study participants stated that e-cigarettes are more refined than traditional cigarettes, which agrees with the notion that e-cigarettes are becoming more socially accepted among the youth 7,26 .…”
Section: Discussionsupporting
confidence: 91%
“…The most frequent reason was the perceived better taste of e-cigarettes compared with traditional cigarettes. In agreement with other studies, around a third of the students considered vaping safer and cheaper than traditional smoking [23][24][25] . Moreover, around one-third of the study participants stated that e-cigarettes are more refined than traditional cigarettes, which agrees with the notion that e-cigarettes are becoming more socially accepted among the youth 7,26 .…”
Section: Discussionsupporting
confidence: 91%
“…The results indicating that 38% of the surveyed populations who use E cigarette were dependent on it revealing a concerning level of dependency. The observed dependency rate of 38% aligns with findings from other studies globally, highlighting a consistent trend of significant e-cigarette dependence across diverse populations (Alsanea et al, 2022). The subgroup analysis indicating that 27.7% of the population is at high risk of e-cigarette dependency emphasizes the urgency for tailored intervention strategies.…”
Section: Discussionsupporting
confidence: 85%
“…Of the study participants, 62.1% had an inadequate awareness about e-cigarettes, and 56% thought they were less harmful. In a study on health professional students’ understanding of e-cigarettes in Saudi Arabia, Alsanea S et al [ 71 ] found that participants had misconceptions, considered e-cigarettes as a tool for quitting smoking, and knew hardly anything about the harmful effects of e-cigarettes. According to a research article by Kurdi R et al [ 72 ], university students in Qatar who use e-cigarettes felt that they are safer than traditional cigarettes, and most of them thought that using e-cigarettes would help them avoid using conventional cigarettes.…”
Section: Discussionmentioning
confidence: 99%